Pengaruh Product Quality, Brand Trust Dan Brand Image Terhadap Loyalitas Pelanggan Honda Civic (Studi Kasus pada pelanggan Honda Civic di Kabupaten Malang) - Ahmad Rizal Said; Muhammad Ridwan Basalamah; Andi Normala (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine and analyze the influence simultaneously or partially on Product Quality, Brand Trust, and Brand Image on Customer Loyalty of Honda Civic. This type of research is explanatory or explanatory research using a quantitative approach. The sample in this study were 50 respondents. The sampling technique used in this research is snowball sampling. Analysis of the data used is descriptive statistics and multiple linear regression analysis. The results of this study indicate that the variables Product Quality, Brand Trust and Brand Image have a positive and significant effect on customer loyalty. Partially what can be seen from the results of the t test shows that the Product Quality variable has a positive and significant effect on customer loyalty. The Brand Trust variable has a positive and significant effect on Customer Loyalty, while the Brand Image variable has a positive and significant impact on Customer Loyalty. Based on these calculations, it can be concluded that partially the Product Quality, Brand Trust, and Brand Image variables have a positive and significant effect on Customer Loyalty. The results of statistical data analysis show that Product Quality, Brand Trust, and Brand Image have a positive and significant effect on Customer Loyalty. This shows that good product quality will determine customer perceptions of product performance which will have an impact on loyalty and a strong brand image provides an advantage over other competitors so that customers will trust the brand. Keywords: Product Quality, Brand Trust, Brand Image and Customer Loyalty